2005
DOI: 10.1084/jem.20041674
|View full text |Cite
|
Sign up to set email alerts
|

BAFF is produced by astrocytes and up-regulated in multiple sclerosis lesions and primary central nervous system lymphoma

Abstract: We report that B cell–activating factor of the tumor necrosis factor (TNF) family (BAFF) is expressed in the normal human brain at ∼10% of that in lymphatic tissues (tonsils and adenoids) and is produced by astrocytes. BAFF was regularly detected by enzyme-linked immunosorbent assay in brain tissue lysates and in normal spinal fluid, and in astrocytes by double fluorescence microscopy. Cultured human astrocytes secreted functionally active BAFF after stimulation with interferon-γ and TNF-α via a furin-like pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
316
3
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 442 publications
(337 citation statements)
references
References 23 publications
14
316
3
4
Order By: Relevance
“…For example, Ittah et al (32) demonstrated that BAFF is not expressed by TNF␣-stimulated salivary gland epithelial cells from patients with primary Sjögren's syndrome. In another study, BAFF expression and production by astrocytes were not up-regulated by TNF␣ (10). The fact that in our model, TNF␣ is unlikely to function as an inducer of BAFF synthesis by FLS, could not be due to impaired activity of TNF␣ insofar as FLS release high concentrations of IL-6 in response to TNF␣.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…For example, Ittah et al (32) demonstrated that BAFF is not expressed by TNF␣-stimulated salivary gland epithelial cells from patients with primary Sjögren's syndrome. In another study, BAFF expression and production by astrocytes were not up-regulated by TNF␣ (10). The fact that in our model, TNF␣ is unlikely to function as an inducer of BAFF synthesis by FLS, could not be due to impaired activity of TNF␣ insofar as FLS release high concentrations of IL-6 in response to TNF␣.…”
Section: Discussioncontrasting
confidence: 38%
“…This cytokine, which is present at low levels in normal human brain tissue as compared with lymphoid tissue, is constitutively produced by astrocytes (10). Its production is increased in sclerotic cerebral lesions and in cerebral primary lymphomas.…”
mentioning
confidence: 99%
“…Meningeal inflammation in MS may include Bcell-rich collections of immune cells [97], and secretory products of MS B cells have been shown to be cytotoxic to oligodendrocytes [98]. Astrocytes have been implicated in support of B-cell survival in inflamed MS CNS, through expression of the B-cell-activating factor of the TNF family [99]. Ongoing research is directed at elucidating effects of glial cells on B-cell subsets and, in turn, effects of B-cell regulatory and effector (Breg and Beff, respectively) products on CNS cells.…”
Section: B-cell Cytokines and B-cell/t-cell Interactions In Msmentioning
confidence: 99%
“…BAFF and APRIL play crucial roles in B cell‐development, survival, and production of immunoglobulin by binding with receptors 1. Three BAFF receptors have been identified: BCMA, TACI, and BAFF‐R 2.…”
Section: Introductionmentioning
confidence: 99%
“…However, MRI characteristics are not specific for PCNSL, and in most cases diagnosis requires a neuropathological examination 6. Krumbholz et al established astrocytes as BAFF producers and suggested that CNS‐derived BAFF may promote B cell survival in PCNSL 1. Thaler et al reported that CSF and serum TACI and BCMA levels were higher in patients with PCNSL than in control patients 7…”
Section: Introductionmentioning
confidence: 99%